What role do Bourdieu´s capital forms play in the success of recent graduates? Supported by Icelandic evidence - Steinarsdóttir, Anna Sigurrós (2021)
The study, based on Bourdieu's forms of capital, aims to understand if they influence recent graduate success in Iceland, following similar studies. It includes two phases, qualitative (semi-structured interviews) and quantitative (online questionnaires).First, data was gathered from twelve semi-structured interviews and later, an online survey was performed with 106 responses. Content analysis, inferential statistics and SEM were used to understand how recent graduates define and measure success, and how social, cultural and economic capital influence recent graduates success. The main findings are that all forms of capital have a statistically significant effect on perceived graduate success.